Effects of weaning biscuits on the nutritional profile and the cognitive development in preschool children - Pradheepa Subramanian; Nazni Peerkhan; Hasan Abul (BMC, 2010)
Abstract Aim To study the effect of weaning biscuits supplementation of the nutritional parameters and cognitive performance of the selected children. Methods Three primary schools situated in Salem District, Tamilnadu, India were selected. A total number of 150 school children, 61 from primary school I, 46 from primary school II and 43 from primary school III comprised the study sample. About 80 primary school children with Grade II malnutrition were selected for the experimental study. Home diet without any supplementation was followed by Group I (n = 20, control group), potato flour biscuit was supplemented to Group II (n = 20), wheat biscuits was given to Group III (n = 20) and ragi biscuits were given to Group IV (n = 20) for the period of 3 months. Parameters like anthropometric measurements, hemoglobin content clinical picture and cognitive performance were analyzed before and after supplementation. Results Results about Group I (control group) showed no significant difference in height, weight and clinical picture and cognitive performance after three months on their home diet. In Group II, III and IV significant increase in all the above parameters was noticed. More increase was found in Group II children supplemented with potato flour biscuits for a period of 3 months. About cognitive performance better results was obtained in Group II followed by Group III (supplemented with wheat biscuits) and Group IV (supplemented with ragi biscuits). Least was obtained by control group children who are in their home diet. Conclusion All these observations evident that if such weaning biscuits made with potato flour, wheat and Ragi can form a daily ingredient in their diets, it will bring out better all round development of the children.